PENGARUH MAKRO EKONOMI TERHADAP NON PERFORMING LOAN BANK SWASTA NASIONAL - Rendy Dwi Putra (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
The Purpose of his research is to analyze the influencethe Non-Performing Loan (NPL) in the tenth small private bank by capital in Indonesia in 2009-2015. As some of the factors analyzed in influenceof Non-Performing Loan (NPL): Gross Domestic Product (GDP), Inflation(INF), and Interest Rate of Credit Investment (IRCI). The sample in this study is fifthbank of BUKU 1 that is Mandiri Taspen Pos Bank, Jasa Jakarta Bank, Capital Bank, Index Selindo Bank, and CCB Indonesian Bank, while fifthbank of BUKU 2 that is Mestika Bank, KEB Hana Indonesian Bank, Mayapada Bank, MNC International Bank, and Sinarmas Bank. The data used is the annual data released by the bank and Secondary data were obtained directly from the World Bank and Bank Indonesia. This research was conducted with quantitative approach and analyzed using Ordinary Least Square (OLS). The result of this research show that the Gross Domestic Product (GDP) had a negative and not significantimpact on the Non-Performing Loan (NPL); the Inflation(INF) had a negative and significantimpact on the Non-Performing Loan (NPL); and the Interest Rate of Credit Investment (IRCI) had a positive and not significant impact on the Non-Performing Loan (NPL)